Development and Validation of The Modified Falls Efficacy Scale Indonesian Version - Martha, Anastasia Putu; Djoar, Raditya Kurniawan (Jurusan Keperawatan FIKES UNSOED, 2020)
Fear of falling causes a decrease quality of life of elderly. Tool for identified fear of falling is Modified FES I adopted from FES I. FES-I needs to be developed because it’s used for people with disabilities so it’s not sensitive to assess fear of falling in elderly. Content validation and internal consistency of tools need to be done. Original instrument was translated into Bahasa by two linguists and health professionals. Translation results were translated back into English by two other translators. After considering language equality, content validity was tested by 7 geriatricians (physiotherapists, lecturers and doctors). 105 elderly (±76 years old) in nursing homes were selected by proportional random sampling. Validity index (CVI) and Cronbach's alpha are used to analyze the questionnaire. Modified FES-I contains 16 items. CVI results was > 0.8 for item level and> 0.9 for the entire questionnaire. Questions 1, 3, 4, 5, 10, and 11 need to be modified according to the culture and conditions in Indonesia and 12 need to be modified because it overlaps with number 11. Internal consistency is very good (0.957). The results showed, Modified FES-I is valid and can be used to measure fear of falling in elderly in Indonesia